Curriculum-Based Measurement of Reading: Accuracy of Recommendations From Three-Point Decision Rules. Issue 3 (1st September 2016) - Van Norman, Ethan R.; Christ, Theodore J.
Abstract: Despite their widespread use, there is little research to support the accuracy of curriculum-based measurement of reading progress monitoring decision rules. The purpose of this study was to investigate the accuracy of a common data point decision rule. This study used a three-point rule with a goal line of 1.50 words read correctly per minute (WRCM) across six levels of true growth (range = 0–3 WRCM), two levels of dataset quality or residual (5 and 10 WRCM), and 13 levels of data collection (range = 3–15 weeks). We estimated the probability of a correct decision as well as the probability of each outcome (change instruction, increase the goal, maintain instruction) across each condition with probability theory and a spreadsheet program. In general, results indicate that recommendations are often inaccurate. Further, the probability of a correct recommendation is below chance in most situations. Results of multiple regression analyses indicate that residual, duration, and true growth interacted to influence decision accuracy. Results are discussed along with implications for future research and practice.